The Role of CXCR3 and Associated Chemokines in the Development of Atherosclerosis and During Myocardial Infarction - Szentes, Veronika; Gazdag, Mária; Szokodi, István; Dézsi, Csaba A. (Frontiers in Immunology, 2018)
The chemokine receptor CXCR3 and associated CXC chemokines have been extensively investigated in several inflammatory and autoimmune diseases as well as in tumor development. Recent studies have indicated the role of these chemokines also in cardiovascular diseases. We aimed to present current knowledge regarding the role of CXCR3-binding chemokines in the pathogenesis of atherosclerosis and during acute myocardial infarction.